Frase Endonsentris Bahasa Saluan - Syamsuddin Syamsuddin; Efendi Dg. Palawa; Idris Patekkai; Moh. Tahir M. Said; Ali Karim (Aksara, 2022)
This research describes the structure of the endocentric phrases of the Saluan language. The problem is formulated in the form of a question, namely how is the internal structure of the endocentric phrases of Saluan. The theoretical study uses the views of Lyons (1968), Cook (1969), Verhaar (1981 and 1999), Parera (1983), Ramlan (1987), Ahmad HP (1997), and Djajasudarma (2003). The method of collecting data uses listening techniques and speaking techniques based on the opinions of Samarin (1988), Djajasudarma (1993), and Sudaryanto (1993). In data analysis, distributional analysis techniques were used through the views of Djajasudarma (1993). The results showed that the structure of Saluan ensocentric phrases has two types of construction, namely: (1) attributive phrases with patterns H+T, T+H, and, T+H+T. These three patterns can be found in the noun, adjective, verb, and adverb word classes. (2) coordinating phrases with construction types consisting of: (a) additive, (b) appositive, (c) alternative, and (d) coordinating elements consisting of: (i) additive coordinator and (ii) contrastive coordinator. AbstrakPenelitian ini mendeskripsikan struktur frase endosentris bahasa Saluan. Masalah dirumuskan dalam bentuk pertanyaan, yakni bagaimanakah struktur internal frase endosentris bahasa Saluan. Dalam kajian teori digunakan pandangan Lyons (1968), Cook (1969), Verhaar (1981 dan 1999), Parera (1983), Ramlan (1987), Ahmad HP (1997), dan Djajasudarma (2003). Metode pengumpulan data menggunakan teknik simak dan teknik cakap dengan bardasarkan pendapat Samarin (1988), Djajasudarma (1993), dan Sudaryanto (1993). Dalam analisis data digunakan teknik kajian distribusional melalui pandangan Djajasudarma (1993). Hasil penelitian menunjukkan bahwa struktur frase ensosentris bahasa Saluan memiliki dua tipe konstruksi, yakni: (1) frase atributif dengan pola H+T, T+H, dan, T+H+T. Ketiga pola tersebut dapat ditemukan pada kelas kata nomina, ajektiva, verba, dan adverbia. (2) frase koordinatif dengan tipe konstruksi yang terdiri atas: (a) aditif, (b) apositif, (c) alternatif, dan (d) unsur-unsurnya berkoordinatif yang terdiri atas: (i) koordinator aditif dan (ii) koordinator kontrastif.